Consonantes con segunda articulación palatal y labial alofónicas en la lengua arabela (záparo) - Jimenez Peña, Jhon (2022)
This paper is a first exploratory description of consonants with palatal and labial secondary articulation of allophonic nature in Arabela (Záparo) language not previously reported. In this study, the behavior of three nominalizing suffixes is examined to notice the existence of phonetic palatalized and labialized sounds: {–ha} 'he or what he is or does', {–ka} 'agent' and {–nu} 'infinitive'. To this effect, the methodology used for data collection that helped to identify the specific contexts where roots and these suffixes interact in order to observe their allophony is proposed. In addition, data were analyzed and interpreted from the acoustic-phonetic perspective. Also, the status of the issue of this class of allophonic sounds in Arabela is presented in the discussion section and, finally, the conclusions of this research.